Coal-based hard carbon negative electrode material and preparation method thereof, negative electrode plate and sodium ion battery
Through etching and water vapor activation, the coal-based hard carbon negative electrode material formed with a core-shell structure is solved, and the irreversible loss of capacity and safety of hard carbon negative electrode material during high current charging is achieved, and high conductivity, oxidation resistance and corrosion resistance are improved.
Patent Information
- Application Number
- CN202510062551.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
During the high current charging process, hard carbon negative electrode materials are prone to precipitation of sodium metal dendrites, causing irreversible capacity loss, and even causing internal short circuits and safety issues of the battery, affecting its commercial application.
By etching the pre-carbonized low-carbon material and weakly activate water vapor, the mixed gas of water vapor and inert gas is used as carrier gas to transport liquid chain hydrocarbon compounds, and undergo strong activation treatment to form a pore structure and an amorphous carbon layer, repair the surface defects of the carbon, and obtain a coal-based hard carbon negative electrode material with a core-shell structure.
This process improves the conductivity, oxidation and corrosion resistance of coal-based hard carbon negative electrode materials, enhances the capacity properties of sodium ions and the stability of the battery, simplifies the process flow, and reduces costs.
Smart Images

Figure CN119873787A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a coal-based hard carbon negative electrode material and a preparation method thereof, a negative electrode sheet and a sodium ion battery. Background Art
[0002] Sodium has the advantages of abundant reserves, wide distribution and low price, so sodium-ion batteries are considered to be one of the most promising large-scale electrochemical energy storage systems.
[0003] As the key material of sodium-ion batteries, the development of high-performance and low-cost negative electrode materials is an important step in promoting the commercialization of sodium-ion batteries. Among the many sodium storage negative electrode materials, hard carbon materials have the advantages of low sodium storage potential, high sodium storage capacity, wide source of raw materials and low cost. They are currently the mainstream negative electrode materials for sodium-ion batteries. However, since the working potential of hard carbon materials is extremely close to the precipitation potential of sodium metal, sodium ions are enriched on the surface of hard carbon materials during high-current charging, which easily precipitates metallic sodium dendrites, causing irreversible loss of capacity, and may even pierce the diaphragm, causing internal short circuits in the battery, unstable performance, and causing safety issues such as thermal runaway and combustion and explosion of the battery, affecting the commercial application of hard carbon materials.
[0004] Therefore, there is an urgent need to provide a method for preparing a hard carbon negative electrode material to solve the problem of low capacity and unstable performance of the hard carbon negative electrode material. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a coal-based hard carbon negative electrode material and a preparation method thereof, a negative electrode plate and a sodium ion battery. The present invention first etches the pre-carbonized low-carbon material so that the surface of the particles is etched, and then uses water vapor to weakly activate it at high temperature, and then uses a mixed gas including water vapor and an inert gas as a carrier gas to transport liquid chain hydrocarbon compounds, thereby forming a pore structure on the one hand, and performing surface deposition on the other hand, repairing carbon surface defects, and repairing surface damage caused by water vapor activation, and forming an amorphous carbon layer on the surface of the material, and finally obtaining a coal-based hard carbon negative electrode material with a core-shell structure. This process not only overcomes the defects of a single carbon material, so that the coal-based hard carbon negative electrode material has high conductivity, strong anti-oxidation and anti-corrosion properties, but also the process is simple and easy to implement during industrial amplification, and can avoid cumbersome process flows.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a coal-based hard carbon negative electrode material, the preparation method comprising the following steps: (1) Pre-carbonizing the raw coal to obtain a pre-carbonized low-carbon material, and then mixing the pre-carbonized low-carbon material with an etching solution to obtain an etching material.
[0007] (2) introducing water vapor to weakly activate the etching material, then introducing a liquid hydrocarbon compound with the aid of a carrier gas to strongly activate the etching material after the weak activation treatment, then cooling it, and then carbonizing it to obtain the coal-based hard carbon negative electrode material; Wherein, the carrier gas includes water vapor and inert gas.
[0008] The present invention first etches the pre-carbonized low-carbon material so that the surface of the particles is etched, providing favorable conditions for subsequent activation, and then uses water vapor to perform weak activation at high temperature to open the surface of the coal particles, and then uses a mixed gas including water vapor and an inert gas as a carrier gas to transport liquid chain hydrocarbon compounds for strong activation, thereby forming a pore structure on the one hand, and performing surface deposition on the other hand, which can repair the defect sites on the surface of the pore structure and effectively close the pore size, promote the formation of ink bottle pores, closed pores and slender narrow pores, and then promote the rapid deintercalation of sodium ions and the increase of sodium storage active sites, improve the capacity properties of sodium ions, and form an amorphous carbon layer on the surface of the material, and finally obtain a coal-based hard carbon negative electrode material with a core-shell structure. This process not only overcomes the defects of a single carbon material, so that the coal-based hard carbon negative electrode material has high conductivity, strong anti-oxidation and anti-corrosion properties, but also the process is simple and easy to implement during industrial amplification, and can avoid cumbersome process flows.
[0009] It should be noted that the present invention does not limit the type of inert gas, and illustratively, it may be nitrogen or the like.
[0010] Preferably, the raw coal in step (1) comprises any one of anthracite, lean coal, lean coal, coking coal, fat coal, gas coal, slightly sticky coal, non-sticky coal, long flame coal and lignite, or a combination of at least two thereof, preferably long flame coal.
[0011] Preferably, the raw coal in step (1) is first subjected to pulverization, purification, water washing and drying in sequence before being subjected to pre-carbonization.
[0012] Preferably, the purification solution used in the purification process is a composite acid solution.
[0013] Preferably, the composite acid solution includes at least two of hydrochloric acid, hydrofluoric acid and an oxidizing acid. Exemplary, for example, it can be a combination of hydrochloric acid and hydrofluoric acid, a combination of hydrochloric acid and an oxidizing acid, a combination of hydrofluoric acid and an oxidizing acid, or a combination of hydrochloric acid, hydrofluoric acid and an oxidizing acid.
[0014] In the present invention, the composite acid solution is used for purification, which can achieve the effects of purifying and oxidatively modifying the raw coal in one step. Specifically, hydrochloric acid and hydrofluoric acid gradually eliminate the ash in the coal while leaving pores or channels. At this time, with the cooperation of the oxidizing acid, the problem of air infiltrating into the pores or channels, which causes the oxidizing acid to be unable to oxidize the inside of the particles, can be effectively avoided.
[0015] Preferably, the concentration of the hydrochloric acid is 1-10 mol / L, for example, 1 mol / L, 3 mol / L, 5 mol / L, 7 mol / L or 9 mol / L.
[0016] Preferably, the concentration of the hydrofluoric acid is 1-10 mol / L, for example, 1 mol / L, 3 mol / L, 5 mol / L, 7 mol / L or 9 mol / L.
[0017] Preferably, the concentration of the oxidizing acid is 5-10 mol / L, for example, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L or 10 mol / L.
[0018] Preferably, the oxidizing acid comprises any one of concentrated nitric acid, dilute nitric acid, concentrated sulfuric acid, permanganic acid, dichromic acid, hypochlorous acid, chloric acid, chlorous acid, perchloric acid or nitrous acid, or a combination of at least two thereof.
[0019] Preferably, the purification treatment temperature is 60-100°C, for example, 60°C, 70°C, 80°C, 90°C or 100°C.
[0020] In the present invention, the appropriate treatment temperature is beneficial to the purification, which is beneficial to promote the acidification reaction and effectively remove the ash and impurities of the coal.
[0021] Preferably, the mass ratio of the raw coal to the composite acid solution is 1:(2-10), for example, it can be 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10, etc.
[0022] In the present invention, the raw coal and the composite acid solution are in an appropriate mass ratio, which can realize effective deashing while controlling the cost.
[0023] Preferably, the washing step comprises: The purified carbon material is washed with water to remove residual acid on the surface of the carbon material until it is neutral.
[0024] Preferably, the water washing process is accompanied by centrifugation.
[0025] Preferably, during the water washing process, the centrifugal speed is 500-1500 rpm, for example, it can be 500 rpm, 1000 rpm or 1500 rpm.
[0026] Preferably, the washing time is 60-120 min, for example, 60 min, 80 min, 100 min or 120 min.
[0027] Preferably, the drying temperature is 80-100°C, for example, 80°C, 90°C or 100°C.
[0028] Preferably, the drying time is 12-24 hours, for example, 12 hours, 14 hours, 16 hours, 18 hours or 20 hours.
[0029] Preferably, the temperature of the pre-carbonization treatment in step (1) is 350-650°C, for example, 350°C, 450°C, 550°C or 650°C.
[0030] In the present invention, the pre-carbonization treatment at a specific temperature is helpful for the full escape of volatiles, and is beneficial for the thermal transformation of oxygen functional groups, and the removal of active groups from the surface of the material, thereby forming carbon microcrystals and pore structures required for hard carbon.
[0031] Preferably, the pre-carbonization treatment time in step (1) is 12-24 hours, for example, it can be 12 hours, 16 hours, 20 hours or 24 hours.
[0032] Preferably, the heating rate of the pre-carbonization treatment in step (1) is 2-5°C / min, for example, 2°C / min, 3°C / min, 4°C / min or 5°C / min.
[0033] Preferably, the etching solution in step (1) comprises alkaline solution.
[0034] The present invention uses alkaline solution as etching solution, which is helpful to micro-etch the surface of the pre-carbonized carbon material and promote the subsequent penetration of water vapor activation.
[0035] Preferably, the concentration of the etching solution in step (1) is 15-20wt%, for example, 15wt%, 16wt%, 17wt%, 18wt% or 20wt%.
[0036] In the present invention, an etchant with a suitable concentration can fully exert the etching effect of the alkali.
[0037] Preferably, the alkali solution includes any one of sodium hydroxide, potassium hydroxide, barium hydroxide, ammonium hydroxide or calcium hydroxide, or a combination of at least two thereof.
[0038] Preferably, the mass ratio of the pre-carbonized low-carbon material to the etching solution in step (1) is 1:(2-10), for example, it can be 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10.
[0039] In the present invention, the appropriate mass ratio of the pre-carbonized low-carbon material and the etching solution helps to improve the surface properties of the pre-carbonized material while effectively controlling the cost.
[0040] Preferably, during the weak activation treatment in step (2), the flow rate of water vapor is 10-100 L / min, for example, 10 L / min, 30 L / min, 50 L / min, 70 L / min, 90 L / min or 100 L / min.
[0041] Preferably, the time of the weak activation treatment in step (2) is 5-10 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min.
[0042] Preferably, the temperature of the weak activation treatment in step (2) is 800-1000°C, for example, 800°C, 850°C, 900°C, 950°C or 1000°C.
[0043] The present invention uses water vapor to perform weak activation treatment at the above temperature, which can open the surface of coal particles and lay the foundation for subsequent strong activation treatment.
[0044] Preferably, in the carrier gas of step (2), the volume ratio of the inert gas to the water vapor is 1:(1-3), for example, it can be 1:1, 1:2 or 1:3.
[0045] Preferably, the volume of the carrier gas in step (2) is 10-100 L / min, for example, 10 L / min, 30 L / min, 50 L / min, 70 L / min, 90 L / min or 100 L / min, etc., preferably 50-80 L / min.
[0046] In the present invention, the carrier with a suitable gas volume can effectively activate the inside of the coal particles, and at the same time can carry liquid chain hydrocarbon compounds to form a stable coating carbon layer at the activation etching position.
[0047] Preferably, the liquid chain hydrocarbon compound in step (2) includes aliphatic hydrocarbon compounds and / or aromatic hydrocarbon compounds.
[0048] Preferably, the aliphatic hydrocarbon compound includes any one of n-hexane, cyclohexane or pentane, or a combination of at least two of them.
[0049] Preferably, the aromatic hydrocarbon compound comprises any one of toluene, benzene or xylene or a combination of at least two thereof. Preferably, the temperature of the strong activation treatment in step (2) is 800-1000°C, for example, 800°C, 850°C, 900°C, 950°C or 1000°C.
[0050] In the present invention, strong activation treatment at a suitable temperature is helpful for the reaction between water vapor and carbon atoms of condensed aromatic hydrocarbons in coal, and is beneficial for the deposition of chain hydrocarbon compounds.
[0051] Preferably, the time of the strong activation treatment in step (2) is 3-8 h, for example, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h.
[0052] Preferably, the heating rate of the strong activation treatment in step (2) is 1-10°C / min, for example, it can be 1°C / min, 3°C / min, 5°C / min, 7°C / min, 9°C / min or 10°C / min.
[0053] Preferably, the environmental pressure of the strong activation treatment in step (2) is 1-1.5 KPa, for example, it can be 1 KPa, 1.2 KPa or 1.5 KPa.
[0054] In the present invention, strong activation treatment is carried out under a suitable pressure, which is beneficial to maintaining the activation and aromatic hydrocarbon molecule deposition environment in the reaction device and isolating the influence of external atmosphere.
[0055] Preferably, the cooling process in step (2) includes: first programmed cooling and then natural cooling.
[0056] Preferably, the temperature after programmed cooling is 200-300°C, for example, 200°C, 250°C or 300°C.
[0057] Preferably, the temperature after natural cooling is 20-50°C, for example, 20°C, 25°C, 30°C, 40°C or 50°C.
[0058] Preferably, the temperature of the carbonization treatment in step (2) is 1100-1600°C, for example, it can be 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C.
[0059] Preferably, the carbonization treatment time in step (2) is 1-10 h, for example, 1 h, 3 h, 5 h, 7 h, 9 h or 10 h.
[0060] Preferably, the preparation method comprises the following steps: (a) The raw coal is crushed to a particle size D50 of 4-30 μm (for example, 4 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc.), and then the obtained crushed material is placed in a composite acid solution, and purified for 3-6 hours at 60-100°C and 100-600 rpm (for example, 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm or 600 rpm, etc.) to obtain a purified material; the obtained crushed material is stirred at 500-1500 rpm. The purified material is centrifugally washed with water for 60-120 minutes, and dried at 80-100°C for 12-24 hours to obtain a dried material; the dried material is pre-carbonized in an inert atmosphere (nitrogen or argon, etc.), the pre-carbonization temperature is 350-650°C, the time is 12-24 hours, and the heating rate is 2-5°C / min to obtain a pre-carbonized low-carbon material, and then the pre-carbonized low-carbon material is crushed, and then mixed with an alkali solution with a concentration of 15-20wt%, and etched for 8-12 hours, and then dried to obtain an etched material.
[0061] The mass ratio of the raw coal to the composite acid solution is 1:(2-10), the composite acid solution includes hydrochloric acid, hydrofluoric acid and oxidizing acid in a volume ratio of 1:1:(1-3), the concentration of hydrochloric acid is 1-10 mol / L, the concentration of hydrofluoric acid is 1-10 mol / L, and the concentration of oxidizing acid is 5-10 mol / L; the mass ratio of the pre-carbonized low-carbon material to the alkali solution is 1:(2-10).
[0062] (b) introducing water vapor at a flow rate of 10-100 L / min for a time of 5-10 min at a temperature of 800-1000°C, and then using a mixture of an inert gas and water vapor in a volume ratio of 1:(1-3) as a carrier gas, and the volume of the carrier gas is 10-100 L / min, and introducing a liquid chain hydrocarbon compound to strongly activate the etched material after the weak activation treatment, the temperature of the strong activation treatment is 800-1000°C, the time is 3-8h, the heating rate is 1-10°C / min, the ambient pressure is 1-1.5 KPa, and then programmed to cool to 200-300°C, and then naturally cooled to 20-50°C, and then carbonized in an inert atmosphere for 1-10h, the temperature of the carbonization treatment is 1100-1600°C, to obtain the coal-based hard carbon negative electrode material.
[0063] In a second aspect, the present invention provides a coal-based hard carbon negative electrode material, wherein the coal-based hard carbon negative electrode material is prepared by the preparation method described in the first aspect.
[0064] The coal-based hard carbon negative electrode material is a core-shell structure, wherein the core is a modified coal-based hard carbon material and the shell is an amorphous carbon layer.
[0065] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the coal-based hard carbon negative electrode material as described in the second aspect.
[0066] In a fourth aspect, the present invention provides a sodium ion battery, comprising the negative electrode sheet as described in the third aspect.
[0067] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0068] Compared with the prior art, the present invention has the following beneficial effects: The present invention first etches the pre-carbonized low-carbon material so that the surface of the particles is etched, providing favorable conditions for subsequent activation, and then uses water vapor to perform weak activation at high temperature to open the surface of the coal particles, and then uses a mixed gas including water vapor and an inert gas as a carrier gas to transport liquid chain hydrocarbon compounds for strong activation, thereby forming a pore structure on the one hand, and performing surface deposition on the other hand, which can repair the defect sites on the surface of the pore structure and effectively close the pore size, promote the formation of ink bottle pores, closed pores and slender narrow pores, and then promote the rapid deintercalation of sodium ions and the increase of sodium storage active sites, improve the capacity properties of sodium ions, and form an amorphous carbon layer on the surface of the material, and finally obtain a coal-based hard carbon negative electrode material with a core-shell structure. This process not only overcomes the defects of a single carbon material, so that the coal-based hard carbon negative electrode material has high conductivity, strong anti-oxidation and anti-corrosion properties, but also the process is simple and easy to implement during industrial amplification, and can avoid cumbersome process flows. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 This is a process flow chart provided for Example 1 of the present invention.
[0070] Figure 2 This is a SEM image of the coal-based hard carbon negative electrode material provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0071] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0072] Example 1 This embodiment provides a method for preparing a coal-based hard carbon negative electrode material, and its process flow chart is as follows: Figure 1 As shown, the preparation method comprises the following steps: (1) The raw coal (i.e., long flame coal) is crushed to a particle size D50 of 15 μm, and then the obtained crushed material is placed in a composite acid solution, and purified for 4 hours under stirring conditions of 80°C and 300 rpm to obtain a purified material; the purified material is centrifuged and washed with water at 1000 rpm for 80 minutes, and dried at 90°C for 18 hours to obtain a dried material; the dried material is pre-carbonized in a nitrogen atmosphere, the pre-carbonization temperature is 500°C, the time is 18 hours, and the heating rate is 4°C / min to obtain a pre-carbonized low-carbon material, and then the pre-carbonized low-carbon material is crushed, and then mixed with an alkali solution with a concentration of 18wt%, and etched for 8 hours, and then dried to obtain an etched material.
[0073] Among them, the mass ratio of raw coal and composite acid solution is 1:6, the composite acid solution includes hydrochloric acid, hydrofluoric acid and concentrated nitric acid in a volume ratio of 1:1:2, the concentration of hydrochloric acid is 5 mol / L, the concentration of hydrofluoric acid is 5 mol / L, and the concentration of concentrated nitric acid is 10 mol / L; the mass ratio of pre-carbonized low-carbon material and alkali solution is 1:2, and the alkali solution is potassium hydroxide.
[0074] (2) The etching material is weakly activated by introducing water vapor at a flow rate of 70 L / min for 5 min at a temperature of 900°C, and then a mixture of nitrogen and water vapor in a volume ratio of 1:2 is used as a carrier gas. The carrier gas has a gas volume of 65 L / min, and a liquid hydrocarbon compound is introduced to strongly activate the etching material after the weak activation treatment. The temperature of the strong activation treatment is 900°C, the time is 5 h, the heating rate is 5°C / min, and the ambient pressure is 1.2 KPa. The temperature is then programmed to decrease to 300°C, and then naturally decreased to 35°C. Subsequently, a carbonization treatment is carried out in a nitrogen atmosphere for 5 h. The temperature of the carbonization treatment is 1300°C to obtain the coal-based hard carbon negative electrode material.
[0075] Wherein, the liquid chain hydrocarbon compound is n-hexane.
[0076] Figure 2 The SEM image of the coal-based hard carbon negative electrode material provided in this embodiment is shown. It can be seen from the figure that the coal-based hard carbon negative electrode material prepared in this embodiment presents a typical hard carbon irregular granular shape, and the surface of the hard carbon is smooth due to the deposition of liquid chain hydrocarbon compounds.
[0077] Example 2 This embodiment provides a method for preparing a coal-based hard carbon negative electrode material, the preparation method comprising the following steps: (1) The raw coal (i.e., long flame coal) is crushed to a particle size D50 of 4 μm, and then the obtained crushed material is placed in a composite acid solution, and purified for 6 hours at 60°C and 600 rpm to obtain a purified material; the purified material is centrifuged and washed with water at 500 rpm for 120 minutes, and dried at 80°C for 24 hours to obtain a dried material; the dried material is pre-carbonized in a nitrogen atmosphere at a temperature of 350°C for 24 hours and a heating rate of 2°C / min to obtain a pre-carbonized low-carbon material, and then the pre-carbonized low-carbon material is crushed, and then mixed with an alkali solution with a concentration of 16 wt%, and etched for 12 hours, and then dried to obtain an etched material.
[0078] Among them, the mass ratio of raw coal and composite acid solution is 1:2, the composite acid solution includes hydrochloric acid, hydrofluoric acid and dilute nitric acid in a volume ratio of 1:1:1, the concentration of hydrochloric acid is 1 mol / L, the concentration of hydrofluoric acid is 1 mol / L, and the concentration of dilute nitric acid is 5 mol / L; the mass ratio of pre-carbonized low-carbon material and alkali solution is 1:2, and the alkali solution is sodium hydroxide.
[0079] (2) The etching material is weakly activated by introducing water vapor at a flow rate of 60 L / min for 10 min at a temperature of 1000°C, and then a mixture of nitrogen and water vapor in a volume ratio of 1:1 is used as a carrier gas. The carrier gas volume is 50 L / min, and a liquid chain hydrocarbon compound is introduced to strongly activate the etching material after the weak activation treatment. The temperature of the strong activation treatment is 1000°C, the time is 8 h, the heating rate is 5°C / min, and the ambient pressure is 1.0 KPa. The temperature is then programmed to decrease to 300°C, and then naturally decreased to 30°C. Subsequently, a carbonization treatment is carried out in a nitrogen atmosphere for 10 h. The temperature of the carbonization treatment is 1100°C to obtain the coal-based hard carbon negative electrode material.
[0080] Among them, the liquid chain hydrocarbon compound is pentane.
[0081] Example 3 This embodiment provides a method for preparing a coal-based hard carbon negative electrode material, the preparation method comprising the following steps: (1) The raw coal (i.e., long flame coal) is crushed to a particle size D50 of 30 μm, and then the obtained crushed material is placed in a composite acid solution, and purified for 3 hours under stirring conditions of 100°C and 100 rpm to obtain a purified material; the purified material is centrifuged and washed with water at 1500 rpm for 60 minutes, and dried at 100°C for 12 hours to obtain a dried material; the dried material is pre-carbonized in a nitrogen atmosphere at a temperature of 650°C, a time of 12 hours, and a heating rate of 5°C / min to obtain a pre-carbonized low-carbon material, and then the pre-carbonized low-carbon material is crushed, and then mixed with an alkali solution with a concentration of 19 wt%, and etched for 10 hours, and then dried to obtain an etched material.
[0082] Among them, the mass ratio of raw coal and composite acid solution is 1:10, the composite acid solution includes hydrochloric acid, hydrofluoric acid and concentrated nitric acid in a volume ratio of 1:1:3, the concentration of hydrochloric acid is 1-10mol / L, the concentration of hydrofluoric acid is 1-10mol / L, and the concentration of concentrated nitric acid is 8mol / L; the mass ratio of pre-carbonized low-carbon material and alkali solution is 1:2, and the alkali solution is sodium hydroxide.
[0083] (2) The etched material is weakly activated by introducing water vapor at a flow rate of 90 L / min for 8 min at a temperature of 950°C, and then a mixture of nitrogen and water vapor in a volume ratio of 1:3 is used as a carrier gas. The carrier gas volume is 80 L / min, and a liquid chain hydrocarbon compound is introduced to strongly activate the etched material after the weak activation treatment. The temperature of the strong activation treatment is 950°C, the time is 3 h, the heating rate is 10°C / min, the ambient pressure is 1.3 KPa, and then the temperature is programmed to decrease to 300°C, and then naturally decreased to 50°C, followed by carbonization treatment in a nitrogen atmosphere for 1 h. The carbonization treatment temperature is 1600°C to obtain the coal-based hard carbon negative electrode material.
[0084] Wherein, the liquid chain hydrocarbon compound is toluene.
[0085] Example 4 The difference between this embodiment and embodiment 1 is that the concentration of the alkali solution is 10 wt %.
[0086] The rest of the preparation methods and parameters were the same as those in Example 1.
[0087] Example 5 The difference between this embodiment and embodiment 1 is that the concentration of the alkali solution is 25wt%.
[0088] The rest of the preparation methods and parameters were the same as those in Example 1.
[0089] Example 6 The difference between this embodiment and embodiment 1 is that the mass ratio of the pre-carbonized low-carbon material to the alkali solution is 1:12.
[0090] The rest of the preparation methods and parameters were the same as those in Example 1.
[0091] Example 7 The difference between this embodiment and embodiment 1 is that the mass ratio of the pre-carbonized low-carbon material to the alkali solution is 1:1.
[0092] The rest of the preparation methods and parameters were the same as those in Example 1.
[0093] Example 8 The difference between this embodiment and embodiment 1 is that the gas volume of the carrier gas in step (2) is 5 L / min.
[0094] The rest of the preparation methods and parameters were the same as those in Example 1.
[0095] Example 9 The difference between this embodiment and embodiment 1 is that the gas volume of the carrier gas in step (2) is 150 L / min.
[0096] The rest of the preparation methods and parameters were the same as those in Example 1.
[0097] Example 10 The difference between this embodiment and embodiment 1 is that the temperature of the strong activation treatment in step (2) is 700°C.
[0098] The rest of the preparation methods and parameters were the same as those in Example 1.
[0099] Embodiment 11 The difference between this embodiment and embodiment 1 is that the temperature of the strong activation treatment in step (2) is 1100°C.
[0100] The rest of the preparation methods and parameters were the same as those in Example 1.
[0101] Example 12 The difference between this embodiment and embodiment 1 is that the environmental pressure of the strong activation treatment in step (2) is 0.5 KPa.
[0102] The rest of the preparation methods and parameters were the same as those in Example 1.
[0103] Embodiment 13 The difference between this embodiment and embodiment 1 is that the environmental pressure of the strong activation treatment in step (2) is 2.0 KPa.
[0104] The rest of the preparation methods and parameters were the same as those in Example 1.
[0105] Comparative Example 1 The difference between this comparative example and Example 1 is that the liquid chain hydrocarbon compound in step (2) is replaced by a gaseous chain hydrocarbon compound, namely methane.
[0106] The rest of the preparation methods and parameters were the same as those in Example 1.
[0107] Comparative Example 2 The difference between this comparative example and Example 1 is that no alkaline solution is added in step (1), that is, no etching treatment is performed.
[0108] The rest of the preparation methods and parameters were the same as those in Example 1.
[0109] Performance Testing 1. Physical and chemical property test of coal-based hard carbon, including: (1) Tap density test: 10g sample is loaded and tapped 6300 times on a tap density meter to test the tap density; (2) Powder compaction density test: The powder compaction density of coal-based hard carbon negative electrode material is tested on a compaction density meter at a pressure of 369 MPa.
[0110] 2. Test of electrochemical properties of coal-based hard carbon: The coal-based hard carbon negative electrode material provided in the above embodiments and comparative examples is made into a negative electrode sheet, and then assembled with a positive electrode sheet, a separator and an electrolyte to obtain a sodium ion battery. The specific steps include: Coal-based hard carbon negative electrode material, conductive carbon black, PVDF, sodium carboxymethyl cellulose and solvent water are mixed in a certain proportion to obtain a negative electrode slurry, which is then coated on a copper foil and dried to obtain a negative electrode plate; the negative electrode plate, the diaphragm (i.e., polyethylene diaphragm) and the positive electrode plate (metal sodium plate) are stacked in sequence to make a battery cell; an electrolyte (i.e., an organic solvent and a sodium salt, wherein the organic solvent is ethylene carbonate and the sodium salt is NaClO4) is injected into the cell, which is then sealed to obtain a button-type sodium ion battery.
[0111] The first efficiency and reversible capacity of the above sodium-ion battery were tested.
[0112] The test conditions are: according to the charge and discharge system of 0.1C charge / 0.1C discharge, the window voltage is set to 0-2.0V, and the first efficiency and reversible capacity properties of the battery are tested.
[0113] The test results are shown in Table 1.
[0114] Table 1
[0115] analyze: It can be seen from the above table that the preparation method provided by the present invention not only overcomes the defects of single carbon material, so that the coal-based hard carbon negative electrode material has high conductivity, strong antioxidant and corrosion resistance, but also the obtained core-shell structured coal-based hard carbon negative electrode material has high vibration and compaction performance, considerable capacity and first coulombic efficiency.
[0116] It can be seen from Examples 1 and 4-5 that if the concentration of the alkali solution is too low, the etching effect on the surface of the pre-carbonized low-carbon material is not obvious, affecting the subsequent activation effect of water vapor activation on the inside; if the concentration of the alkali solution is too high, the alkali solution enters the material and destroys the material structure and internal properties, and the material strength is reduced.
[0117] It can be seen from Example 1 and Examples 6-7 that if the mass ratio of pre-carbonized low-carbon material and alkali solution is too small, effective etching cannot be achieved; if the mass ratio of pre-carbonized low-carbon material and alkali solution is too large, there is no significant difference. A large amount of alkali may cause the strength of the material to be too low or the alkalinity of the material to be too high, causing corrosion to the equipment.
[0118] It can be seen from Example 1 and Examples 8-9 that if the amount of carrier gas is too small, the surface repair effect is poor, defects exist on the carbon surface, and the capacity is low; if the carrier gas velocity is too large, the large pores cannot be closed after carbonization, the initial efficiency of hard carbon is low, and there is a risk of blowing material.
[0119] It can be seen from Examples 1 and 10-11 that if the temperature of the strong activation treatment is too low, it is not conducive to the deposition of chain hydrocarbon compounds and the capacity is low; if the temperature of the strong activation treatment is too high, it is not conducive to the deposition and repair of chain hydrocarbon molecules.
[0120] It can be seen from Example 1 and Examples 12-13 that if the environmental pressure of the strong activation treatment is too small, it will be easily affected by external gases, affecting the activation effect and further affecting the capacity properties of coal-based hard carbon; if the environmental pressure of the strong activation treatment is too large, the requirements for the equipment will be higher and the equipment cost will be higher.
[0121] It can be seen from Example 1 and Comparative Example 1 that if the liquid chain hydrocarbon compound in step (2) is replaced by a gaseous chain hydrocarbon compound, the gaseous hydrocarbon compound has a poor deposition and repair effect on the defective positions on the hard carbon surface, resulting in poor reversible capacity and first-effect properties.
[0122] It can be seen from Example 1 and Comparative Example 2 that if no alkali solution is added in step (1), that is, no etching treatment is performed, the electrochemical performance is significantly worse than that of Example 1.
[0123] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a coal-based hard carbon negative electrode material, characterized in that: The preparation method comprises the following steps: (1) pre-carbonizing the raw coal to obtain a pre-carbonized low-carbon material, and then mixing the pre-carbonized low-carbon material with an etching solution to obtain an etching material; (2) introducing water vapor to weakly activate the etching material, then introducing a liquid hydrocarbon compound with the aid of a carrier gas to strongly activate the etching material after the weak activation treatment, then cooling it, and then carbonizing it to obtain the coal-based hard carbon negative electrode material; Wherein, the carrier gas includes water vapor and inert gas.
2. The preparation method according to claim 1, characterized in that: The raw coal in step (1) includes any one of anthracite, lean coal, lean coal, coking coal, fat coal, gas coal, slightly sticky coal, non-sticky coal, long flame coal, and lignite, or a combination of at least two thereof; And / or, before the raw coal is pre-carbonized in step (1), it is first crushed, purified, washed and dried in sequence; The purification liquid used in the purification process is a composite acid solution; The composite acid solution includes at least two of hydrochloric acid, hydrofluoric acid and an oxidizing acid; The purification treatment temperature is 60-100°C; The mass ratio of the raw coal to the composite acid solution is 1:(2-10).
3. The preparation method according to claim 1, characterized in that: The temperature of the pre-carbonization treatment in step (1) is 350-650°C; And / or, the pre-carbonization treatment time in step (1) is 12-24 hours; And / or, the heating rate of the pre-carbonization treatment in step (1) is 2-5°C / min.
4. The preparation method according to claim 1, characterized in that: The etching solution in step (1) includes alkaline solution; The alkali solution includes any one of sodium hydroxide, potassium hydroxide, barium hydroxide, ammonium hydroxide or calcium hydroxide, or a combination of at least two thereof; And / or, the etching solution concentration in step (1) is 15-20wt%; And / or, the mass ratio of the pre-carbonized low-carbon material to the etching solution in step (1) is 1:(2-10).
5. The preparation method according to claim 1, characterized in that: During the weak activation treatment in step (2), the flow rate of water vapor is 10-100 L / min; And / or, the duration of the weak activation treatment in step (2) is 5-10 min; And / or, the temperature of the weak activation treatment in step (2) is 800-1000°C; And / or, in the carrier gas of step (2), the volume ratio of the inert gas to the water vapor is 1:(1-3); And / or, the gas volume of the carrier gas in step (2) is 10-100 L / min; And / or, the liquid chain hydrocarbon compound in step (2) includes aliphatic hydrocarbon compounds and / or aromatic hydrocarbon compounds; The aliphatic hydrocarbon compound includes any one of n-hexane, cyclohexane or pentane, or a combination of at least two thereof; The aromatic hydrocarbon compound includes any one of toluene, benzene or xylene, or a combination of at least two thereof; And / or, the temperature of the strong activation treatment in step (2) is 800-1000°C; And / or, the duration of the strong activation treatment in step (2) is 3-8 hours; And / or, the heating rate of the strong activation treatment in step (2) is 1-10°C / min; And / or, the environmental pressure of the strong activation treatment in step (2) is 1-1.5 KPa.
6. The preparation method according to claim 1, characterized in that: The cooling process in step (2) includes: firstly programmed cooling and then natural cooling; And / or, the temperature of the carbonization treatment in step (2) is 1100-1600°C; And / or, the carbonization treatment time in step (2) is 1-10 hours.
7. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (a) The raw coal is crushed to a particle size D50 of 4-30 μm, and then the obtained crushed material is placed in a composite acid solution, and a purification treatment is performed for 3-6 hours under stirring conditions of 60-100° C. and 100-600 rpm to obtain a purified material; the purified material is centrifugally washed with water at 500-1500 rpm for 60-120 minutes, and dried at 80-100° C. for 12-24 hours to obtain a dried material; the dried material is pre-carbonized in an inert atmosphere, the pre-carbonization temperature is 350-650° C., the time is 12-24 hours, and the heating rate is 2-5° C. / min to obtain a pre-carbonized low-carbon material, and then the pre-carbonized low-carbon material is crushed, and then mixed with an alkali solution with a concentration of 15-20wt%, and an etching treatment is performed for 8-12 hours, and an etched material is obtained after drying; The mass ratio of the raw coal to the composite acid solution is 1:(2-10), the composite acid solution comprises hydrochloric acid, hydrofluoric acid and oxidizing acid in a volume ratio of 1:1:(1-3), the concentration of the hydrochloric acid is 1-10 mol / L, the concentration of the hydrofluoric acid is 1-10 mol / L, and the concentration of the oxidizing acid is 5-10 mol / L; the mass ratio of the pre-carbonized low-carbon material to the alkali solution is 1:(2-10); (b) introducing water vapor at a flow rate of 10-100 L / min for a time of 5-10 min at a temperature of 800-1000°C, then using a mixture of an inert gas and water vapor in a volume ratio of 1:(1-3) as a carrier gas, and the volume of the carrier gas is 10-100 L / min, and introducing a liquid chain hydrocarbon compound to strongly activate the etched material after the weak activation treatment, the temperature of the strong activation treatment is 800-1000°C, the time is 3-8h, the heating rate is 1-10°C / min, the ambient pressure is 1-1.5 KPa, and then the temperature is programmed to decrease to 200-300°C, and then naturally decrease to 20-50°C; finally, a carbonization treatment is carried out in an inert atmosphere for 1-10h, and the temperature of the carbonization treatment is 1100-1600°C to obtain the coal-based hard carbon negative electrode material.
8. A coal-based hard carbon negative electrode material, characterized in that: The coal-based hard carbon negative electrode material is prepared by the preparation method according to any one of claims 1 to 7; The coal-based hard carbon negative electrode material is a core-shell structure, wherein the core is a modified coal-based hard carbon material and the shell is an amorphous carbon layer.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the coal-based hard carbon negative electrode material as claimed in claim 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the negative electrode sheet as claimed in claim 9.
Citation Information
Cited By
Anthracite-based hard carbon negative electrode material for sodium ion battery as well as preparation method and application of anthracite-based hard carbon negative electrode material
CN121872357A